A Three Dimensional Simulation Method of the Gantry Crane - Jingsong LI; Hang Su; Quan Liu (Institute of Advanced Engineering and Science, 2013)
Until now, many companies have developed lots of the port machinery remote monitoring systems. However, these monitoring systems usual display the operating status of the port machinery by the schematic diagram, Legend and data. The presentation of information is unable to describe the status of the large number of port machinery. In order to solve the problem, a three-dimensional simulation method of the gantry crane based on the WPF is proposed. This paper studies WPF technology and 3D modeling techniques, on this basis, proposes a kind of the gantry crane 3D simulation method based on WPF, establishes a new generation monitoring system based on 3D, immersive and interactive real-time simulation environment. This system could simulate the real-time 3D virtual scene of the gantry crane, and real-time 3D analog display port machinery running posture and operating environment. Experiments show that CPU and memory usage rate is low enough when the system is running. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2404